Effects of belief versus experiential discrimination on race-based linked fate. (3rd July 2019) - Lu, Fan; Jones, Bradford
ABSTRACT: Since Michael Dawson first put forward the theory that being targets of racial discrimination increases perceptions of linked fate amongst African Americans, applications of his theory to non-Black and contemporary African Americans have arrived at mixed findings. These inconsistencies may be attributed to different conceptualizations of discrimination and a partiality for personal experiences rather than beliefs about discrimination. Using the 2016 Collaborative Multiracial Post-election Survey, we test the argument both beliefs and experiences with discrimination can affect racial attitudes by comparing how the relationship between beliefs/experiential discrimination and race-based linked fate differs across Black, Latino, Asian, and White Americans. The findings suggest even if non-Whites do not personally experience discrimination, they have beliefs about discrimination towards their racial group, and these beliefs are equally important predictors of their sense of race-based linked fate.